The Eight Beatitudes in the Context of the Spirituality of the Sisters of the Resurrection - Joanna Pyszna (Warszawskie Studia Teologiczne)
In this article, the meaning of the Eight Beatitudes (Mt 5:3–12) has been discussed in the context of the spirituality of the Congregation of the Sisters of the Resurrection. It has been demonstrated how the Resurrection Sisters understand the evangelical Beatitudes and how they carry them out every day. This analysis has been based on the documents of the Congregation (the Rule and the Constitutions), the writings of the Foundresses, Blessed Mother Celina Borzęcka, and the Venerable Servant of God Mother Jadwiga Borzęcka, as well as those of the general superiors. Because of the historical ties between the male and female branch of the community of the Resurrection, references have been made to Fr. Piotr Semenenko and Fr. Adolf Bakanowski. Based on a study of the sources, it has been shown that the Resurrectionist spirituality combines the Paschal Mystery and the ideals of the Eight Beatitudes. The correlation of these two elements is founded on the need for an in-depth internal change to take place, which is necessary to fulfill each Beatitude and participate in the Paschal Mystery.